A construção da ciência no Brasil: um estudo a partir da trajetória de cientistas pioneiros - Oliveira, Maysa Leal de (Universidade Federal de São Carlos, 2019)
Seeking to understand the Brazilian scientific arena and the ethos that constitute its foundations, this study focuses on 61 biographies and testimonies of scientists, gathered in the publication Scientists of Brazil, published in 1998, in a commemorative edition of SBPC’s fiftieth anniversary, the Brazilian Society for the Progress of Science. Taking as a methodological reference the Socio-Hermeneutic Program of the Qualitative School of Madrid, which is linked to the Spanish tradition of qualitative research, we accomplished an interpretative reading of this material, performing a socio-hermeneutical analysis of its 852 pages, resorting the History and configuring it as part of the understanding process. With the analysis, we show the existence of an intimate relationship between science and the brazilian social and political context, tempering it with a variety of local conditions and with intense political pressures, necessarily resulting in specificities. Scientists articulate a series of practices, ideas, values and intersubjective criteria, keywords and implicit and explicit expressions that do not belong to the vocabulary and discourse universe, or could we say, to the epistemological field of modern European science. From the evidence of the texts, we infer the thesis of an alterity, that is, of a peculiar character of the science performed by the Scientists of Brazil, distinguishing it from the science that took place in Europe in the same period, the long twentieth century. Different aspects engender to the existence of a scientific ethos of its own, whose character covers a non-reductionist understanding of science, an interdisciplinary effort and of dialogue with other fields of human knowledge, an openness to the demands of society, a particular scientific pedagogy, an intrinsic moral character and a strong political bent. The alterity is, in the last analysis, in the resistance to the logic of the coloniality of power and the knowledge that subsists in the Brazilian structure.
The construction of science in Brazil: a study starting from of the trajectory of pioneering scientists
Keywords: Estudos CTS; Ciência; Cultura; Brasil; Cientistas; STS Studies; Science; Culture; Brazil; Scientists; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA DO CONHECIMENTO